Transferrable SERS Barcodes (Adv. Mater. Interfaces 17/2022). Issue 17 (14th June 2022) - Sahin, Furkan; Pekdemir, Sami; Sakir, Menekse; Gozutok, Zehra; Onses, Mustafa Serdar
Abstract : Transferrable SERS Barcodes In article number 2200048, Furkan Sahin, Mustafa Serdar Onses, and co‐workers introduce a new approach for the fabrication of security labels that is derived from the combined use of a temporary tattoo approach and ink‐jet printing of a particle‐free reactive silver inks. The resulting barcodes exhibit high SERS activity and can be effectively transferred to a range of different objects such as paintings, chips, and coins.